Life in the spirit : spiritual formation in theological perspective - Kalantzis, George; Greenman, Jeffrey P.; Kalantzis, George (Downers Grove, IL : IVP Academic, 2010)
"This collection of essays will be of special interest to those who serve as pastors, spiritual directors, church ministry leaders and Christian educators. Indeed, it will lead forward anyone wanting a secure foundation for pursuing "a continuing response to the reality of God's grace shaping us into the likeness of Jesus Christ, through the work of the Holy Spirit in the community of faith for the sake of the world," as Jeffrey Greenman writes in chapter one."--Jacket.
Spiritual formation in theological perspective : classic issues, contemporary challenges / Jeffrey P. Greenman -- On getting the spirit back into spirituality / Gordon D. Fee -- Spiritual formation as a natural part of salvation / Dallas Willard -- From the porch to the cross : ancient Christian approaches to spiritual formation / George Kalantzis -- The way and the ways : reflections on Catholic spirituality / Lawrence S. Cunningham -- Evangelical holiness : assumptions in John Owen's theology of christian spirituality / Kelly M. Kapic -- Seeking true religion : early evangelical devotion and Catholic spirituality / D. Bruce Hindmarsh -- Reading Christ into the heart : the theological foundations of Lectio divina / Christopher A. Hall -- Spiritual direction as a navigational aid in sanctification / Susan S. Phillips -- Centering prayer / James C. Wilhoit -- "Renewed in knowledge in the image of our creator" through "psalms, hymns, and songs of the spirit" / Cherith Fee Nordling -- Spiritual formation and the sanctity of life / David P. Gushee -- Theology, spiritual formation and theological education : reflections toward application / Linda M. Cannell.
Description based on online resource; title from PDF title page (EBSCO, viewed October 22, 2015).
"This volume emerged from the [2009 Wheaton Theology Conference]'s dialogue about the theological shape of the contemporary discussion about spiritural formation ..."--Introduction.
Includes bibliographical references and indexes.
Master record variable field(s) change: 050
Keywords: Spiritual formation -- Congresses; RELIGION / Christian Life / General; Spiritual formation; Spiritual formation; Electronic books; Conference papers and proceedings; Electronic books